2000
DOI: 10.1007/s001250050008
|View full text |Cite
|
Sign up to set email alerts
|

Both insulin sensitivity and insulin clearance in children and young adults with Type I (insulin-dependent) diabetes vary with growth hormone concentrations and with age

Abstract: Reductions in insulin sensitivity occur during normal pubertal development and are known to be greater in those with Type I (insulin dependent) diabetes mellitus [1,2]. These changes have been attributed to alterations in insulin action in peripheral tissues [3], and are thought to occur secondary to puberty-associated increases in growth hormone (GH) secretion [4] which are exaggerated in Type I diabetes [5]. Nevertheless, the mechanisms that regulate insulin sensitivity are not clearly defined and could invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 59 publications
5
33
0
3
Order By: Relevance
“…Any differences may be partially due to disparities in residual endogenous insulin secretion between adolescents and children or as a consequence of the size of the Boost meal given, as the adolescents received a larger meal bolus than the children yet received virtually the same amount of insulin per gram of carbohydrate. However, the results are in line with the relatively impaired insulin sensitivity and higher insulin concentrations reported in healthy adolescents (21,22).…”
Section: Safetysupporting
confidence: 83%
“…Any differences may be partially due to disparities in residual endogenous insulin secretion between adolescents and children or as a consequence of the size of the Boost meal given, as the adolescents received a larger meal bolus than the children yet received virtually the same amount of insulin per gram of carbohydrate. However, the results are in line with the relatively impaired insulin sensitivity and higher insulin concentrations reported in healthy adolescents (21,22).…”
Section: Safetysupporting
confidence: 83%
“…In the present study, we did not observe any association between HLA-DQB1 genotypes and response to treatment (data not shown). In children and adolescents, most studies have found a relationship between the early loss of ␤-cell function and young age (1,4,34,35) and regarding the magnitude of insulin resistance during growth and the course of puberty (7,36). In the present study, several of the adolescents had high HbA 1c already at the 1-year follow-up.…”
Section: ö Rtqvist and Associatessupporting
confidence: 54%
“…These findings suggest that the difference in the c-peptide/insulin ratio between the nonrisk and risk groups was not due to a difference in insulin resistance. In addition, the metabolic clearance rate for insulin (MCR-I) (35), represented by the clearance rate of exogenously infused insulin, was similar in the 2 groups ( Figure 4I). This finding suggests that SLC30A8 alters the insulin clearance rate of endogenously secreted insulin.…”
Section: Introductionmentioning
confidence: 81%